Wearable Health Monitoring Device Based on IoT Application for Forklift Driver - Jiba, Ardy Syazzwan; Mazlan, Muhammad Hazli (Evolution in Electrical and Electronic Engineering, 2022)
A factory is a complex building where various house equipment is used to produce various products. Health is very important because it needs to do the daily work. One of the health services applications is the monitoring system of heart rate and body temperature. Examination of the heart rate and body temperature is a common parameter for medical at the workplace to maintain the safety and health condition of the forklift drivers. However, the problem that occurs at the workplace is that forklift drivers are fatigued during work. To solve this problem, a wearable health monitoring device by using IoT application was proposed to monitor the forklift driver’s health condition. This study aims to reduce the factory’s rate of accidents and injuries at the workplace. We measured the fatigue level or health condition by using pulse sensor, LM35 and a force-sensing resistor. These sensors are interfaced with the ESP-32 microcontroller. Wireless data transmission is done by wi-fi modules that are used on IoT platforms such as ThingSpeak. So that the data can be monitored over the period. The test results showed that the success rate of the system in detecting heartbeat of 93.75% and body temperature of 99.01%. The overall accuracy of the system to measure the fatigue level or health condition of the forklift driver is 92.76%. In the future, the heart rate sensor could be used to increase the accuracy of the heart rate. Furthermore, the sending notification system through a mobile could be used to notify the supervisor when out of the coverage area.